Reoperation frequency after transverse preputial Island flap urethroplasty “Duckett’s technique” in treatment of severe hypospadias: A single center study - Li, Jiayi; Liu, Pei; Yang, Zhenzhen; Wang, Xinyu; Fan, Songqiao; Li, Zonghan; Song, Hongcheng; Zhang, Weiping (Frontiers in Pediatrics, 2023)
Purpose: Transverse Preputial Island Flap Urethroplasty (TPIFU) is one of the most common techniques for treating severe hypospadias. Studies on the reoperation frequency after TPIFU is lacking. In the present study, we reported our clinical outcomes of severe hypospadias treated with one-staged TPIFU and analyzed the operation frequency. Methods: We retrospectively analyzed the clinical data of severe hypospadias patients who underwent one-stage TPIFU from December 2018 to December 2019 in the department of Urology at Beijing Children's Hospital. A stepwise approach was used to manage the curvature. Severe hypospadias was defined as those residual curvature was higher than 30° after degloving. Urethroplasty complications included fistula, urethral stricture, and diverticulum. The short-term cure was identified as no complications occurring for 12 months after the date of last-time surgery. The reoperation rate and operation frequency of TPIFU were analyzed. Results: A total of 136 patients who underwent one-stage TPIFU were included in the study. The follow-up after primary urethroplasty ranged from 22 to 50 months. The median age at primary surgery was 22.5 months (range from 13 to 132 months). After primary TPIFU surgery, 53(39%) patients underwent additional surgical interventions to treat postoperative complications. Among them, 24 patients (17.6%) developed fistula, 17 patients (12.5%) developed urethral stricture and 11 patients (8.1%) developed diverticulum. After the second surgery, five patients remained fistula, five patients remained urethral stricture, and seven patients remained diverticulum. Overall, 61% (85 patients) met the cured standard after the primary operation, and the two operations cure rate was 87.5% (119 patients). 91.2% (124 patients) were cured in three operations. Conclusions: Although the complication rates after primary TPIFU were relatively high, more than half of patients achieved short-term cured through a single operation, and the cure rate after two or three operations was acceptable.